2021
DOI: 10.1017/s1368980021000616
|View full text |Cite
|
Sign up to set email alerts
|

Global evaluation of the use of glycaemic impact measurements to food or nutrient intake

Abstract: Objective: Measures of glycaemic impact (e.g., postprandial glucose (PPG), oral glucose tolerance test (OGTT), and glycaemic index (GI)) are used by government health and regulatory agencies and public health associations around the world. The objective of this global review was to identify similarities and differences in the use of glycaemic impact measures for potential considerations for harmonization. Design: A literature and internet search was conducted to identify country governme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In our study, the impact of fiber intake on the overall predictive power of the CQI index for the risk of MetS is not expected to be significant. Dietary recommendations typically emphasize consuming foods with low (< 55) and medium (55–70) GI for better blood sugar control [ 52 ]. Our study found that only 8.5% of the participants had a diet with a GI > 70.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the impact of fiber intake on the overall predictive power of the CQI index for the risk of MetS is not expected to be significant. Dietary recommendations typically emphasize consuming foods with low (< 55) and medium (55–70) GI for better blood sugar control [ 52 ]. Our study found that only 8.5% of the participants had a diet with a GI > 70.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence supports DGA guidance to consume foods high in dietary fiber and whole grains. The GI is not included by any national food agency in major food-based dietary guidelines (FBDGs) ( 37 ), though some countries allow GI labeling ( 38 ).…”
Section: Dietary Guidelines For Americans Gi and Health Outcomesmentioning
confidence: 99%
“…Glucose load is a more accurate way of predicting and expressing the effect and amounts of different nutrients (Salmeron et al, 1997;UW, 2018). The glycemic index values are affected by a number of factors, including the variety and ripeness of food, the method of processing, cooking processes, and food storage, in addition to food components and the presence of nutrients other than carbohydrates such as fats, proteins, organic acids, dietary fiber, resistant starch, as well as substances Antinutrients and improved food additives (Lal et al, 2021and Trumbo, 2021and Haini et al, 2022 .…”
Section: Introductionmentioning
confidence: 99%